An approach to psychosocial health among middle-aged and older people by remote sharing of photos and videos from family members not living together: A feasibility study - Noguchi, Taiji; Sato, Michi; Saito, Tami (Frontiers in Public Health, 2022)
Background As an approach to the psychosocial health of people in later adulthood, information and communication technology (ICT) is attracting attention. However, because there is still a disparity issue in ICT use, particularly for older people, considering age-friendly digital interventions is important. We examined the feasibility of an intervention by an age-friendly digital service, remote sharing of photos/videos from families not living together, for psychosocial health in middle-aged and older people. Methods This single-arm study recruited Japanese adults aged ≥ 50 years from web-pages of the social service, Mago-Channel (Chikaku Inc., Japan). Participants used this service for three months to receive photos/videos from the smartphones of their families not living together on a device set up on their home TVs and watched them there. Families not living together were encouraged to send photos/videos at least once a week, but no other restrictions on their lives, including their interactions, were imposed. After three months, the level of user satisfaction and changes in psychosocial health were assessed. Results Finally, 115 participants were included, and 106 completed the intervention; the dropout rate from the intervention was low (7.8%), and satisfaction with the program was high, indicating high feasibility. While depressive symptoms and loneliness did not change markedly, satisfaction with the relationship of families living together increased significantly, and social interactions improved, including those with families not living together. Conclusions High feasibility of this age-friendly digital intervention and its potential benefits on social relationships were shown, encouraging further trials with a confirmatory study design.